PENGARUH CAMPURAN EKSTRAK ANTOSIANIN BERAS HITAM (Oryza sativa L.) DAN EKSTRAK PROTEIN KEDELAI HITAM (Glycine max (L)Merr.) TERHADAP PROFIL LIPID DAN STATUS ANTIOKSIDAN PLASMA TIKUS DISLIPIDEMIA - , Aprilita K. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Dyslipidemia is a risk factor for health because of its contribution to oxidative stress and development of atherosclerosis. From the previous study, the mixture of 54 mg/kg body weight black rice anthocyanin extract (BRAE) and 3,75 g/kg body weight black soybean protein extract (BSPE) gave a significant lipid profile improvement in dyslipidemic rats. But the effect of more concentration of BRAE that was added in BSPE on lipid profile improvement was unclear. In this research, the effect of BRAE at dosages 54, 72, and 90 mg/kg body weight that was added in 3,75 g/kg body weight BSPE on lipid profile, cholesterol atherogenic index, antioxidant status of plasma, and histology of liver of dyslipidemic rats, was evaluated. The results showed that the addition of 54, 72, or 90 mg/kg body weight BRAE in 3,75 g BSPE/kg body weight that were consumed by dyslipidemic rats for 28 days gave positive improvements on lipid profile by decreased the level of